ANALISIS PERATURAN MENTERI PENDIDIKAN DAN KEBUDAYAAN REPUBLIK INDONESIA NOMOR 22 TAHUN 2016 TENTANG STANDAR PROSES PENDIDIKAN DASAR DAN MENENGAH SERTA IMPLIKASINYA DALAM PEMBELAJARAN PAI DI SEKOLAH - Tatang Hidayat; Aceng Kosasih (Muróbbî: Jurnal Ilmu Pendidikan, 2019)
Learning process, as one of the core activities in education, is very prominent in realizing national education goals. However, in reality, despite the standard education process has been formulated, the learning process in Indonesia is still poorly developed. The purpose of this discussion is to analyze the regulations of the Minister of Education and Culture of the Republic of Indonesia Number 22 Year 2016 regarding process standards in Primary and Secondary Education and their implications on Islamic Religious Education (PAI) learning in schools. This study uses a qualitative approach and analytical method. Based on the results of the discussion, the primary and secondary education process standards listed in the regulation Number 22 Year 2016 are reliable and comprehensive. The learning principle with a scientific approach has implications on the wholeness of PAI learning process, as the subject is required to be understood comprehensively, not partially. To accomplish this, PAI teachers must use approaches, strategies, methods, techniques, tactics and learning models that are in harmony with the learning material that is delivered, so that an effective and efficient learning process will be achieved.